Determination of the Occurrence of bla SHV gene in Multidrug Resistant Klebsiellapneumoniae isolated from Babylon province - Sarah Raheem Hamza; Hassan Fadhil Naji (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background and Objective:Klebsiella pneumoniae is an opportunistic pathogen that repeatedly causes various diseases. This bacterium is resistant to many commonly used antibiotics.Multidrug-resistant (MDR) K. pneumoniae produces extended-spectrum β-lactamases (ESBLs), which are a serious issue that needs to be controlled with efficient infection-control techniques. Globally, the prevalence of clinical isolates varies greatly and is evolving rapidly. Therefore, the objectives of this research were to determine the occurrence of thebla SHV1 gene in K.pneumonia isolates and to find the susceptibility of the isolates toβ-lactamaseantibiotics, It shows the pathogenicity of these bacteria in Babylon province and their rate as well as their severity. Methods:Six hundred clinical samples which included urine, burn, and sputum of patients being treated in Babylon hospitals were collected. The specimens were cultivated on MacConkey agar and eosin methylene blue agar, and then incubated at 37 C° for 24 hr. Morphological features, biochemical tests, and Vitek 2 compact were used to identify the K. pneumoniae isolates. The antibiotic susceptibility tests and the biofilm formation were also performed. Results:Fifty-six isolates of K. pneumoniae were isolated and identified. The results revealed that the isolates were resistant to cefotaxime, ceftazidime, ampicillin,and imipenem (100%). The lowest resistance of these isolates to antibiotics was tokanamycin (44%), while the biofilm formation rate was (41%). The PCR assay showedthat 52 (93%) of the isolates had the blaSHV gene while four isolates lack this gene. Conclusion:The emergence of antibiotic resistance in K. pneumoniae is a major global health concern that is an inadvertent result of present medical procedures. Therefore, research into managing multidrug-resistant K. pneumoniae is necessary to lower the incidence and severity of infections.